2017
DOI: 10.14710/jpki.12.1.115-133
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Berhubungan Dengan Perilaku Ibu Hamil Dalam Merencanakan Persalinan Untuk Pencegahan Komplikasi Di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang

Abstract: ABSTRAKData kematian maternal yang diperoleh dari Dinas Kesehatan Kota Semarang  tahun 2012 menunjukkan bahwa Puskemas Bandarharjo menempati urutan teratas sepanjang tahun 2009-2012. Salah satu upaya terobosan untuk percepatan penurunan AKI adalah Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) dengan stiker. Penelitian ini merupakan penelitian kuantitatif, jenis penelitian explanatory research, dengan rancangan cross sectional. Hasil penelitian menunjukkan ibu hamil yang memiliki perencanaan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
4
1
1
Order By: Relevance
“…This study is not in line with the research of Halim [5], the results of bivariate analysis showed that a statistical test with a significance level of 5% was obtained p = 0.550, which means that statistically there was no relationship between education and HIV examination behavior. Research Setiyawati and Meilani [6] is not in line with this study that there is no relationship between the levels of education with HIV test behavior in pregnant women.…”
Section: Discussioncontrasting
confidence: 92%
“…This study is not in line with the research of Halim [5], the results of bivariate analysis showed that a statistical test with a significance level of 5% was obtained p = 0.550, which means that statistically there was no relationship between education and HIV examination behavior. Research Setiyawati and Meilani [6] is not in line with this study that there is no relationship between the levels of education with HIV test behavior in pregnant women.…”
Section: Discussioncontrasting
confidence: 92%
“…Pregnant women with HIV need to do early detection and prevention of their babies. However, in this P7 did not realize that she was infected so that there was a delay in the prevention [24]. The expectations of PLWHA are very dependent on health services, especially in diagnostic tests such as HIV testing or a check on the amount of virus in the blood.…”
Section: The Management Of Sick Pediatric Care and Hiv Testingmentioning
confidence: 97%
“…The division of the roles of mother and father complements each other to meet the needs of sick children. A study by Halim [24] stated that family tasks for preschool age children require parental adaptation because roles are complex. The parents become busy with pre-school child development tasks.…”
Section: The Management Of Sick Pediatric Care and Hiv Testingmentioning
confidence: 99%
“…Ini sesuai dengan penelitian Hidayati & Safitri (2018) yang menyatakan ada hubungan perencanaan persalinan dan pencegahan komplikasi dengan pemilihan penolong persalinan. Perencanaan persalinan yang bisa dilakukan diantaranya adalah perilaku ibu selama menunggu persalinan seperti makanan yang harus dimakan, pantangan makanan dan gerakan gerakan pada ibu hamil yang mempermudah persalinan (Murdiati & Jati, 2017;Mariana, 2018).…”
Section: Pembahasanunclassified